Lyophilization of Liposomal Formulations: Still Necessary, Still Challenging - Silvia Franzé; Francesca Selmin; Elena Samaritani; Paola Minghetti; Francesco Cilurzo (MDPI AG, 2018)
Nowadays, the freeze-drying of liposome dispersions is still necessary to provide a solid dosage form intended for different routes of administration (i.e., parenteral, oral, nasal and/or pulmonary). However, after decades of studies the optimization of process conditions remains still challenging since the freezing and the dehydration destabilize the vesicle organization with the concomitant drug leakage. Starting from the thermal properties of phospholipids, this work reviews the main formulation and process parameters which can guarantee a product with suitable characteristics and increase the efficiency of the manufacturing process. In particular, an overview of the cryo- and/or lyo-protective mechanisms of several excipients and the possible use of co-solvent mixtures is provided. Attention is also focused on the imaging methods recently proposed to characterize the appearance of freeze-dried products and liposome dispersions upon reconstitution. The combination of such data would allow a better knowledge of the factors causing inter-vials variability in the attempt to improve the quality of the final medicinal product.